Migration and pollution - Raghbendra Jha; John Whalley (The University of Western Ontario, Department of Economics, 2003)
We explore the links between migration of labour and location specific (urban) pollution, suggesting a sense in which pollution can be welfare improving. In a conventional Harris-Todaro model of urban-rural migration, individuals migrate so as to equate the expected urban wage (given a downward rigid real wage in the urban sector) to the real wage. Unemployment is endogenously determined. Interpreting unemployment as damage, urban pollution (damage denoted in units of labour) can also support the same equilibrium with the value of damage equal to the value of resources otherwise lost through unemployment. However, if the damage function implies an uninternalized externality (due to urban congestion, for instance), an internalization gain can be realized through the use of a Pigouvian tax (or instrument) that discourages migration. Thus if pollution is introduced into a Harris-Todaro model with no such features, environmental damage displaces unemployment to support a similar outcome. Internalizing the externality then yields a welfare gain. We characterize the optimal Pigouvian tax in such a case and show that it is, in general, non-zero. In this sense, then, pollution can be welfare improving perhaps suggesting an alternative view of congestion and other adverse environmental effects facing urban dwellers in the developing world.
Keywords: O1; O18; J6; Q21; 330; migration; damage; pollution; unemployment; Arbeitsmobilität; Arbeitslosigkeit; Umweltbelastung; Regionales Cluster; Theorie